Single-benzene-based ratiometric fluorescent probe for hydrazine visualization - Kang, Jisoo; An, Jong Min; Seo, Eun Woo; Lee, Jaehui; Huh, Youngbuhm; Park, Chan; Kim, Jaehoon; Kim, Dokyoung (Elsevier BV, 2023)
Hydrazine (N2H4) is a crucial chemical being widely used in various industrial fields. However, hydrazine exposure can cause severe harm to humans, animals, and the natural environment due to its high reactivity and toxicity. In this work, we disclosed a new fluorescent probe for hydrazine detection, utilizing a single benzenebased fluorophore (SBBF). The new hydrazine probe, named HP, reacted explicitly with hydrazine in a short time (<1 min) and had ratiometric emission changes with a large Stokes shift (172 nm). HP also showed high physicochemical stability, which is the most critical characteristic for practical application in environmental conditions. Furthermore, we conducted hydrazine detection experiments across multiple applications, encompassing paper strips, soils, and liquid samples. This study presents a new hydrazine fluorescent probe based on SBBF that holds immense potential for widespread application across various fields.